Bruce Bronzan Press Conference re Candidate for 31st Assembly District at Fresno Hilton Hotel - Watkins, Howard::::::::: (1982)
Close up of Linda Bronzan holding Chloe Bronzan at table Portable high end cassette tape recorder on table